Youths’ Violent Resistance of Necropolitical Landscape of COVID-19 in Nigeria’s Vanishing Foodscapes and Waterscapes - Okorie, V. O.; Okorie, N.; Amusan, L. (My University, 2021)
This article interrogates the necropolitical landscape of COVID-19 in Nigeria. The article explores how the landscape emerges at the intersection of COVID-19 regime and structural violence and materializes in foodscapes and waterscapes of the country. It, also, analyzes ethical quandaries arising as the brutal violence of the regime is amplified by structural violence in places and spaces of residence, recreation, leisure and labor of ordinary people. Using qualitative data derived from primary and secondary sources, the article demonstrates that the necropolitical landscape reconfigures social relationships, meanings and identities embedded in places and spaces where people interact with each other and with food and water to produce youth’s violent resistance as well as varnishing foodscapes and waterscapes. These changes ultimately impose the status of a living-dead on ordinary people in Nigeria. The article concludes that without the provision of adequate palliative, devoid of food fraud, geography of corruption, gender and ethnic-biases to every citizen, the government loses its moral ground to implement its COVID-19 regime. To meet the gap between what Nigeria can afford and what is required to implement the regime, both the government and its financial elites must embrace economic justice. Finally, the government should opt for a modified regime that factors the extant material conditions of the havenots into the arrangement.
Keywords: COVID-19 pandemic; Ethical quandaries; Egoism; Altruism; Necropolitics; Foodscapes